Epistemological implications in pedagogical practice: A study with Basic Education teachers (Research, Society and Development, 2023)
This study presents the results of research aimed at identifying the epistemological conceptions embedded in the pedagogical practice of a group of basic education teachers from a public school located in the city of Santa Maria, RS. The results were obtained through a research instrument (questionnaire) based on the ideas of Porlán, composed of closed-ended Likert scale items. Data analysis was conducted quantitatively using the software "Microsoft Excel" version 2010 and "Statistical Package for Social Sciences" (SPSS) version 22. The results revealed that the empiricist-inductivist conception still prevails among the teachers in basic education at the surveyed school, reaffirming the need for the inclusion of in-depth studies on epistemology in initial and continuing teacher education programs.